Penurunan kafein dan asam klorogenat kopi menggunakan metode microwave-assisted extraction: studi parameter dan evaluasi sensoris: Reduction of caffeine and chlorogenic acid in coffee using microwave-assisted extraction: a study of parameters and sensory evaluation - Yuniati, Yuyun; Pramitha, Asti Rizkiana; Ningtyas, Rosidah Wahyu; Saraswati, Exist; Agustini, Maria (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Healthier coffee is an innovative effort made in response to consumer needs that tend to reduce coffee consumption due to the side effects of caffeine and chlorogenic acid on the human body. This study aims to reduce caffeine and chlorogenic acid by implementing the Microwave-Assisted Solvent Extraction (MASE) method using water as a solvent. In the process of reducing caffeine and chlorogenic acid in coffee, optimization was carried out on the microwave power parameters (300 W and 600 W), the mass ratio of the sample to the solvent (0.100; 0.125; 0.150 g/mL), and the extraction time (2, 4, 6, 8, 10, and 12 minutes). The results showed that the microwave power parameters of 600 W, the mass-solvent ratio of 0.125 and 0.15, and the extraction time of 12 minutes significantly affected the increase in the percentage of caffeine and chlorogenic acid recovery. Coffee products before and after treatment were tested hedonically to obtain assessments from 35 untrained panelists. Through the Kruskal-Wallis and Man Whitney U statistical tests, there was no difference in the aspects of bitterness, acidity, and sweetness. This method can be an option for the coffee industry in producing low-caffeine coffee with high added value and good consumer acceptance.